Structure, Function, and Regulation of the Plasma Membrane Na+/H+ Antiporter Salt Overly Sensitive 1 in Plants - Xie, Qing; Zhou, Yang; Jiang, Xingyu (Frontiers in Plant Science, 2022)
Physiological studies have confirmed that export of Na+ to improve salt tolerance in plants is regulated by the combined activities of a complex transport system. In the Na+ transport system, the Na+/H+ antiporter SOS1 is the main protein that functions to excrete Na+ out of plant cells. In this paper, we review the structure and function of the Na+/H+ antiporter and the physiological process of Na+ transport in SOS signaling pathway, and discuss the regulation of SOS1 during phosphorylation activation by protein kinase and the balance mechanism of inhibiting SOS1 antiporter at molecular and protein levels. In addition, we carried out phylogenetic tree analysis of SOS1 proteins reported so far in plants, which implied the specificity of salt tolerance mechanism from model plants to higher crops under salt stress. Finally, the high complexity of the regulatory network of adaptation to salt tolerance, and the feasibility of coping strategies in the process of genetic improvement of salt tolerance quality of higher crops were reviewed.